2008
DOI: 10.5713/ajas.2008.80190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cattle Slurry on Growth, Biomass Yield and Chemical Composition of Maize Fodder

Abstract: An experiment was carried out to study the effect of cattle slurry on maize fodder (Zea mays) production. Maize fodder was produced at 4 cattle slurry levels T 0 (0 ton/ha), T 1 (10 ton/ha), T 2 (12 ton/ha) and T 3 (14 ton/ha) in a randomized block design. Agronomic characteristics, plant heights, circumference of stems, number of leaves, leaf area and dry matter yield of maize fodder were measured. Maize plant height and stem circumference were significantly (p<0.01) influenced by the increasing rate of cattl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 13 publications
5
17
0
Order By: Relevance
“…The highest and lowest was achieved by the application of 100% liquid bio-slurry and control treatment, respectively. Nitrogen fertilizer, either organic or inorganic, always affects vegetative growth of the fodder and cereals; and therefore, the increase in the application of liquid bioslurry and yield maximization of kale was in line with the results reported by Rahman et al (2008). Similarly, the increase in dry biomass of kale on the application of biogas slurry in combination of N inorganic fertilizer was in line with the results reported by Yu et al (2010).…”
Section: Dry Biomasssupporting
confidence: 81%
See 1 more Smart Citation
“…The highest and lowest was achieved by the application of 100% liquid bio-slurry and control treatment, respectively. Nitrogen fertilizer, either organic or inorganic, always affects vegetative growth of the fodder and cereals; and therefore, the increase in the application of liquid bioslurry and yield maximization of kale was in line with the results reported by Rahman et al (2008). Similarly, the increase in dry biomass of kale on the application of biogas slurry in combination of N inorganic fertilizer was in line with the results reported by Yu et al (2010).…”
Section: Dry Biomasssupporting
confidence: 81%
“…The lowest number of leaves per plant in the control treatment could be due to the insufficient nitrogen supply of plants and resulting in reduction of plant productivity and thereby reducing the number of leaves per plant (Shangguan et al, 2000). Moreover, the finding is also similar to the results reported by Rahman et al (2008).…”
Section: Number Of Leaves Per Plantsupporting
confidence: 81%
“…The experiment under cattle dung performed better in terms of higher number of leaves plant -1 and mean leaf area in maize. According to Rahman et al (2008), application of cattle slurry did not showed a significant effect on number of leaves but the average leaf area plant -1 was increased significantly. The increase in number of leaves plant -1 and leaf area plant -1 with organic fertilizer application was reported earlier Goenadi (1985).…”
Section: Discussionmentioning
confidence: 99%
“…As stated by Rahman et al (2008), unbalanced use of chemical fertilizers has affected soil health, causing a substantial decrease in soil organic carbon. As a general rule, use of organic fertilizers especially in composted form produces positive effect on soil health and fertility, which consequents increased crop yield on a long-term basis (Mehdizadeh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%